2021
DOI: 10.3390/universe7090350
|View full text |Cite
|
Sign up to set email alerts
|

Analog Particle Production Model for General Classes of Taub-NUT Black Holes

Abstract: We derive a correspondence between the Hawking radiation spectra emitted from general classes of Taub-NUT black holes with that induced by the relativistic motion of an accelerated Dirichlet boundary condition (i.e., a perfectly reflecting mirror) in (1+1)-dimensional flat spacetime. We demonstrate that the particle and energy spectra is thermal at late times and that particle production is suppressed by the NUT parameter. We also compute the radiation spectrum in the rotating, electrically charged (Kerr–Newma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In a very recent paper, Foo et al [36] proposed to study the Hawking radiation in a different way, which is somewhat similar to the Unruh effect [37]. They [36] investigated an accelerated boundary correspondence which mimics the outgoing Hawking radiation produced by a general class of Taub-NUT BHs. It has been shown [36] that if a BH contains the GMM (n) along with the regular matter, the particle production is suppressed by the GMM.…”
Section: Evaporation Of Taub-nut Pbhsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a very recent paper, Foo et al [36] proposed to study the Hawking radiation in a different way, which is somewhat similar to the Unruh effect [37]. They [36] investigated an accelerated boundary correspondence which mimics the outgoing Hawking radiation produced by a general class of Taub-NUT BHs. It has been shown [36] that if a BH contains the GMM (n) along with the regular matter, the particle production is suppressed by the GMM.…”
Section: Evaporation Of Taub-nut Pbhsmentioning
confidence: 99%
“…They [36] investigated an accelerated boundary correspondence which mimics the outgoing Hawking radiation produced by a general class of Taub-NUT BHs. It has been shown [36] that if a BH contains the GMM (n) along with the regular matter, the particle production is suppressed by the GMM. Considering the particle spectrum of the frequencies of the outgoing and incoming modes ω and ω ′ respectively, Foo et al [36] showed that the particle number decays to zero for large values of n (i.e., n close to 1 in G = c = M = 1 unit) for both the regimes: ω ∼ ω ′ and ω << ω ′ .…”
Section: Evaporation Of Taub-nut Pbhsmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been a number of studies that relate different specific black hole models (e.g., the Schwarzschild [ 21 , 22 , 23 , 24 ] case) and their analog moving mirrors, including the extremal Reissner–Nordström (RN) [ 25 , 26 ], extremal Kerr [ 27 ], RN [ 28 ], Taub-NUT [ 29 ] and Kerr [ 30 ] black holes. In addition, de Sitter and anti-de Sitter cosmologies [ 31 ] are also modeled by moving mirror trajectories.…”
Section: Introductionmentioning
confidence: 99%